Wonders of the Omnipotent Creator: An analysis based on Quranic Verses on Creation - Dr. Gulnaz Naeem; Dr. Syed Shahabuddin (Al Basirah, 2020)
Man has been interested in the universe and its wonders since long. Existence of the universe itself is a puzzle and people from different aspects tried to solve the riddle. When we talk about the religious seminaries, their approach is towards divine revelation i.e. Holy Quran from Islamic point of view. According to the Quranic teachings, existence of the universe isn‟t a coincidence, Almighty Allah is the creator of the heaves, earth, all which are inside and outside them. Even He is the creator of the things people know and what they know not. This paper aims to identify the Quranic verses regarding wonders in the creation of universe and what inside is, so that people may think and recognize their Creator and His might instead of the misconception of origin of universe by chances and coincidences. Because by saying or accepting the existence of universe by chance and living beings through evolutionary process means to violate the belief on creation, which leads towards the denial of the Creator.